Bioethics and the right of access to health care - Volnei Garrafa (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2023)
Access to health care is a universal human right and therefore should not be treated as a commodity only accessible to people with the economic means to acquire it. This study adopts a theoretical framework based on UNESCO's Universal Declaration on Bioethics and Human Rights. The discussion first explores the rationale for choosing human rights as a foundation for such an endeavor. Secondly, the notion of equity is presented as an indispensable principle that should be incorporated into such discussions, reinforcing the understanding that unequal people and populations must be treated in a differentiated and compensatory manner, with the aim of seeking true equality based on the humanitarian recognition of every individual's rights, accounting for their needs and differences. Thirdly, the text seeks to address the complex problem of prioritizing the allocation of scarce resources in order to ensure access to health care for as many people as possible. In summary, this article intends to demonstrate that access to health care for all people, regardless of their income level, should be considered to be a universal human right. Beyond the obligations of governments and the private sector to support inclusive programs, there is also a need to acknowledge social movements' legitimate struggles for achieving better living conditions and health outcomes for all people, without exception.